2019
DOI: 10.1186/s13662-019-2449-x
|View full text |Cite
|
Sign up to set email alerts
|

A discrete-time mathematical model of stage-structured mosquito populations

Abstract: This paper proposes a system of difference equations to model mosquito population. In this study, we develop and analyze the stage-structured models which consist of four distinct mosquito metamorphic stages: eggs, larvae, pupae, and adults. First, a model with constant birth rate is studied, and the inherent net reproduction number 0 of the model is derived. If 0 < 1, the extinction equilibrium is globally asymptotically stable. If 0 > 1, there exists a unique positive equilibrium which is uniformly persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Several other researchers reported that if the value of “ R” is greater than 1, the population of the species increases. They further reported that when the value of “ R” is equal to 1, the population of the species remains stable and when this value is less than 1, the population declines and the species goes extinct 44 , 45 . When the quantity of some diet ingredients in Diet 2 was increased (Diet 3) and fed it to larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Several other researchers reported that if the value of “ R” is greater than 1, the population of the species increases. They further reported that when the value of “ R” is equal to 1, the population of the species remains stable and when this value is less than 1, the population declines and the species goes extinct 44 , 45 . When the quantity of some diet ingredients in Diet 2 was increased (Diet 3) and fed it to larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we investigate the dynamical properties of malaria in the human and mosquito populations with limited resource. Also, it should be noticed that only the adult female mosquitoes bite human beings and animals in order to take blood meals, and the male mosquitoes feed only on plant juices [12,19,25,30]. Female mosquitoes, which are involved in the transmission of vector-borne diseases will not lay viable eggs without blood meals.…”
Section: Introductionmentioning
confidence: 99%